2005
DOI: 10.1081/prg-45765
|View full text |Cite
|
Sign up to set email alerts
|

The Renin-Aldosterone Response to Stimulation and Suppression During Normal Pregnancy

Abstract: Objective-During normal pregnancy, studies have shown increased activity of the reninangiotensin-aldosterone system (RAAS) and a dissociation of plasma renin activity (PRA) and aldosterone (Aldo) evidenced by a greater increase in Aldo relative to PRA. The aims of this study were to examine the RAAS response to stimulation by upright posture and suppression by saline infusion and to investigate the PRA-Aldo dissociation under these two conditions. Methods-We studied 24 healthy normotensive women (mean ± standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
(20 reference statements)
3
13
1
1
Order By: Relevance
“…Interestingly, the difference in the measured levels of natriuretic peptides can be related to the degree of activation of the renin-angiotensin-aldosterone system (RAAS) that plays a vital role during normal pregnancy [35], and appears differently activated in the various types of hypertension in pregnancy. Studies carried out during normal pregnancy have shown a peculiar activation of the RAAS as evidenced by a disproportionate increase in PRA relative to PA levels [36]. In the present study, the higher levels of both ANP and BNP have been observed in patients showing a lower PRA/ aldosterone ratio (see ''Results'').…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, the difference in the measured levels of natriuretic peptides can be related to the degree of activation of the renin-angiotensin-aldosterone system (RAAS) that plays a vital role during normal pregnancy [35], and appears differently activated in the various types of hypertension in pregnancy. Studies carried out during normal pregnancy have shown a peculiar activation of the RAAS as evidenced by a disproportionate increase in PRA relative to PA levels [36]. In the present study, the higher levels of both ANP and BNP have been observed in patients showing a lower PRA/ aldosterone ratio (see ''Results'').…”
Section: Discussionsupporting
confidence: 52%
“…Aldosterone is particularly responsive to slight changes in volume during pregnancy because volume expansion has been shown to suppress its production (67). In contrast, deoxycorticosterone, which is produced through extra-adrenal hydroxylation of progesterone (68), is not suppressible with a dexamethasone infusion (69).…”
Section: Electrolyte Balancementioning
confidence: 99%
“…These changes in Na + trend may be related to the renin-angiotensin-aldosterone system (RAAS) of the mare that directly controls Na + excretion, internal homeostasis and blood pressure. The effects of pregnancy on RAAS function have been investigated in humans (Weir et al, 1975;Bentley-Lewis et al, 2005), dogs (Robb et al, 1970) and mares (Satué and Domingo, 2011). In particular, an increase in aldosterone concentration was found in mares during late pregnancy (Satué and Domingo, 2011).…”
Section: Discussionmentioning
confidence: 99%